Substitute : proposed in lieu of a bill, making further provision to carry into effect the act, entitled "an act, for clearing and improving the navigation of James River, and for uniting the Eastern and Western waters by the James and Kanawha rivers, and for other purposes (LLMC-digital (Series), 1842)
1842? House bill to enact the Act for improving navigation on James River by allowing the James River Company to borrow on the state's credit money to connect the eastern and western waters by the James and Kanawha Rivers. In addition, the act sets forth various procedures and requirements in accordance with this plan; of note, the allowable sum to be borrowed was left blank in this version.